2017
DOI: 10.3382/ps/pew490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of organic or inorganic zinc on carbonic anhydrase activity in eggshell formation and quality of aged laying hens

Abstract: This study evaluated the effects of different dietary levels and sources of zinc (Zn) on performance and carbonic anhydrase (CA) activity in eggshell formation and quality in aged laying hens. A total of 504 Hy-line Grey layers aged 59 wk were fed a basal diet (Zn, 28.4 mg/kg) for 4 wks, then randomly allocated to 7 groups that were fed a basal diet or a basal diet supplemented with inorganic (ZnSO4·H2O) or organic (amino acid metals, 9.58%) Zn at 35, 70, or 140 mg Zn per kg of feed for 6 weeks. Each group had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 31 publications
3
34
2
Order By: Relevance
“…Mao and Lien (2017) supplementation of laying hens diets with 80 mg/kg Nano-ZnO had no beneficial influence on FCR. Zhang et al (2017) found that FCR was not affected in Hy-line layers consuming 35, 70, or 140 mg organic or inorganic zinc per kg diet compared to the control group. In addition to, Yıldırım (2017) added 20, 40, 60, 80 and 100 mg Nano-ZnO /kg diet of Super Nick laying hens observed that FCR was non (P>0.05) differences between treatment groups.…”
Section: Feed Conversion Ratiomentioning
confidence: 80%
See 3 more Smart Citations
“…Mao and Lien (2017) supplementation of laying hens diets with 80 mg/kg Nano-ZnO had no beneficial influence on FCR. Zhang et al (2017) found that FCR was not affected in Hy-line layers consuming 35, 70, or 140 mg organic or inorganic zinc per kg diet compared to the control group. In addition to, Yıldırım (2017) added 20, 40, 60, 80 and 100 mg Nano-ZnO /kg diet of Super Nick laying hens observed that FCR was non (P>0.05) differences between treatment groups.…”
Section: Feed Conversion Ratiomentioning
confidence: 80%
“…Likewise, Badawi et al (2017) reported that feed intake of broiler chickens was not significantly affected by supplementation of 40 ppm Nano-ZnO /kg. Also, Zhang et al (2017) found that the average daily feed intake was not affected in Hy-line layers fed diet supplemented with 35, 70, or 140 mg organic or inorganic zinc per kg diet compared to the control group. Yıldırım (2017) observed that supplementation of 20, 40, 60, 80 and 100 mg Nano-ZnO /kg to super Nick laying hens did not affect the feed intake.…”
Section: Feed Intakementioning
confidence: 91%
See 2 more Smart Citations
“…Copper plays critical roles as a co-factor in many enzymes (Davis and Mertz, 1987) relevant to maintaining proper body functions. Because of its many roles, Zn is vitally important in supporting bone and tissue development (Sahraei et al, 2012), egg shell quality (Zhang et al, 2017), as well as in proper functioning of the immune system (Feng et al, 2009; Jarosz et al, 2017; Perez et al, 2017). In pigs, Zn has been reported to help alleviate post-weaning diarrhea (Zhang and Guo, 2009) and high levels of the Zn and Cu have pharmacological relevance in the swine and poultry industries (Pettigrew, 2006; Zhang and Guo, 2007).…”
Section: Introductionmentioning
confidence: 99%